Fun Fotografi on Biodiversitas: Pelatihan Fotografi sebagai Upaya Pelestarian Biodiversitas di Nagari Kasang, Kabupaten Padang Pariaman: Fun Photography on Biodiversity: Photography Training as an Effort to Preserve Biodiversity in Nagari Kasang, Padang Pariaman Regency - Pratama, Sandi Fransisco; Kardiman, Reki; Satria, Rijal; Fadilaturahmah, Fadilaturahmah; Ade, Filza Yulina; Kurniati, Rahmi; Sulaeman, Nabila (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
By 2050, it is estimated that 45% of the world's species and habitats will be lost. "Fun Photography on Biodiversity" is an initiative aimed at enhancing the knowledge and skills of the biodiversity photography community. The activity was conducted in Nagari Kasang, Padang Pariaman Regency, and included methods such as socialization, delivering materials on biodiversity and photography techniques, and field practice. Participants were introduced to local flora and fauna, including endemic species, and were trained in basic photography techniques and ethical practices for documenting nature. Evaluation through pre-tests and post-tests demonstrated significant improvement in participants' understanding of biodiversity and their photography skills. This initiative highlighted the importance of engaging local communities in biodiversity conservation through creative and technology-driven approaches.